L'enchaînement entre les segments thématiques — unités supraphrastiques de la structure informationnelle de discours - Miczka, Ewa (Neophilologica, 2013)
The aim of this paper is to analyse the relations between thematic segments which constitue the intermediate level of information structure in discourse. The information structures are defined as hierarchically organized thematic-rhematic structures and, in their thematic part, the author distinguishes three levels represented by: global theme, theme of thematic segments and theme of sentence. The author focuses her attention on possible thematic-rhematic configurations appearing in the place where thematic segments contact.